Comparative Performance Evaluation of Electric Powertrains in ICE Motorcycle Conversion - Rusli, Muhammad Rizani; Binugroho, Eko Henfri; Nugroho, Mochamad Ari Bagus; Maulana, Himmawan Sabda; Dewanto, Raden Sanggar; Ariwibowo, Teguh Hady; Pramadihanto, Dadet; Jati, Mentari Putri (Advance Sustainable Science Engineering and Technology, 2026)
Electrifying Indonesia’s motorcycle fleet is critical for reducing urban emissions and fossil fuel dependence. This study experimentally evaluates three powertrain configurations—hub motor, continuously variable transmission (CVT), and single-gear ratio—for converting internal combustion engine (ICE) motorcycles to electric two-wheelers (E2W). Using a Honda Vario 125 platform with a 72 V, 3 kW Brushless DC motor and 1.44 kWh lithium-ion battery, performance was assessed via chassis dynamometer and real-world urban road tests. The single-gear ratio configuration demonstrated superior overall performance, achieving 5.15 kW peak wheel power, 188.7 N·m torque, fastest acceleration (0–128 km/h in 22 s), and highest energy efficiency (37.0 km/kWh), enabling a 51.8 km range per charge. The hub motor excelled in top speed, while the CVT consistently underperformed. Benchmarking shows up to 104 % efficiency improvement over prior designs. These results provide quantitative guidance for converters, manufacturers, and policymakers, establishing the single-gear ratio as the optimal solution for urban and commercial E2W applications and supporting sustainable mobility initiatives.